The Meanings Of Verses In Surat Al-Alaq And Their relations To Teaching Arabic (a semantic an educational study)/ الأيات في سورة العلق وعلا قاتها في تعليم اللغة العربية دراسة دلالية وتعليمية - Rahmat Maulana; Bakri Mohammed Bkheet Ahmed (Jurnal Al-Maqoyis, 2022)
This study aims to determine the types and relations of meaning contained in the QS al-'Alaq. This thesis uses a qualitative method that is focused on library research. This research uses a multidisciplinary approach that seeks to discuss and examine objects from several disciplines or relate them to different disciplines, namely semantic studies, and education. The collected data is then processed using qualitative research methods, then the analysis technique and data interpretation used is descriptive-semantic analysis, namely examining the meaning of each word used as an interpretive word to interpret the verses in QS. al-'Alaq is based on theories of semantics in general. The results showed the types of meaning contained in QS. al-'Alaq, consisted of several types of meanings, namely: referential meaning, basic meaning or dictionary meaning (al-ma'na al-asasi wa al-mu'jami), and figurative meaning (al-ma'na al-majazi), and denotative meaning (al-ma'na al-haqiqi). Meanwhile, the relation of meaning between the words or the pronunciation of the Qur'an with the words of its interpretation occurs in four kinds of relations (meaning relationships), namely: Synonym relationships (al-taraduf), Polysemy relationships (ta'addud al-ma'na), the concept of hyponymy and hypernymy (al-Isytimal).